Heterogeneity in the IntergenerationalTransmission of Educational Attainment: Evidence from Switzerland on Natives and Second Generation Immigrants - Bauer, Phillipp; Riphahn, Regina Therese (Journal of Population Economics, 2007)
Refereed Publications: Determinanten des Rentenzugangs - Eine Analyse altersspezifischer Verrentungsraten (Determinants of Retirement Entry - An Analysis of Age-specific Retirement Rates), 1997, Review of Economics (Jahrbuch für Wirtschaftswissenschaften) 48(1), 133-147 (with Peter Schmidt). Disability Retirement and Unemployment - Substitute Pathways for Labor Force Exit?, 1997, Applied Economics 29(5), 551-561. The Determinants of Child Mortality in the Philippines: Estimation of a Structural Model, 1997, Journal of Development Economics 56(2), 281-305 (with David K. Guilkey). Immigrant Participation in the German Welfare Program, 1998, Finanzarchiv 55(2), 163-185. Income and Employment Effects of Health Shocks - A Test Case for the German Welfare State, 1999, Journal of Population Economics 12(3), 363-389. Labor Force Transitions of Older Married Couples in Germany, 1999, Labour Economics 6(2), 229-251 (with David M. Blau). Disability Retirement Among German Men in the 1980s, 1999, Industrial and Labor Relations Review 52(4), 628-647. Geringfügige Beschäftigung: Arbeitsmarktwirkungen und Reformoptionen, 1999, Review of Economics (Jahrbuch für Wirtschaftswissenschaften) 50(3), 213-229 (with Clemens Fuest and Bernd Huber). Explaining Applications to the U.S. Disability Program. A Semiparametric Approach, 1999, Journal of Human Resources 35(1), 82-115 (with Brent Kreider). Fertility Assimilation of Immigrants: Evidence from Count Data Models, 2000, Journal of Population Economics 13(2), 241-261 (with Jochen Mayer). Is the Local Business Tax a User Tax? An Empirical Investigation for Germany, 2001, Journal of Economics and Statistics (Jahrbücher für Nationalökonomie und Statistik) 221(1), 13-41 (with Clemens Fuest). Rational Poverty or Poor Rationality? The Takeup of Social Assistance Benefits, 2001, Review of Income and Wealth 47(3), 379-398. [ pdf-download ] Behavioral Effects of Probation Periods: An Analysis of Worker Absenteeism, 2001, Journal of Economics and Statistics (Jahrbücher für Nationalökonomie und Statistik) 221(2), 179-201 (with Anja Thalmaier). [ pdf-download ] Residential Location and Youth Unemployment: The Economic Geography of School-To-Work Transitions, 2002, Journal of Population Economics 15(1), 115-135. [ pdf-download ] Employment Effects of Payroll Taxes - An Empirical Test for Germany, 2002, Applied Economics 34(7), 865-876 (with Thomas K. Bauer). [ pdf-download ] Incentive Effects in the Demand for Health Care: A Bivariate Panel Count Data Estimation, 2003, Journal of Applied Econometrics 18(4), 387-405 (with Achim Wambach and Andreas Million). [ pdf-download ] Cohort Effects in the Educational Attainment of Second Generation Immigrants in Germany: An Analysis of Census Data, 2003, Journal of Population Economics 16(4), 711-737. [ pdf-download ] Employment Protection and Effort Among German Employees, 2004, Economics Letters 85(3), 353-357. [ pdf-download ] Immigrant Participation in Social Assistance Programs: Evidence from German Guestworkers, 2004, Applied Economics Quarterly 50(4), 329-362. [ pdf-download ] Temporary Contracts and Employee Effort, 2005, Labour Economics 12(3), 281-299 (with Axel Engellandt). [ pdf-download ] Item Non-response on Income and Wealth Questions, 2005, Empirical Economics 30(2), 521-538 (with Oliver Serfling). [ pdf-download ] The Effect of Employment Protection on Worker Effort. A Comparison of Absenteeism During and After Probation, 2005, Journal of the European Economic Association 3(1), 120-143 (with Andrea Ichino).[ pdf-download ] Are there Diverging Time Trends in the Educational Attainment of Nationals and Second Generation Immigrants? [former title: Dissimilation? The Educational Attainment of Second Generation Immigrants], 2005 Journal of Economics and Statistics (Jahrbücher für Nationalökonomie und Statistik) 225(3), 325-346. [ pdf-download ] Survey item nonresponse and its treatment, 2006, Allgemeines Statistisches Archiv 90(1), 213-228 (with Susanne Rässler). [ pdf-download ] Timing of school tracking as a determinant of intergenerational transmission of education, 2006, Economics Letters 91(1), 90-97 (with Philipp Bauer). [ pdf-download ] Education and its intergenerational transmission: country of origin-specific - evidence for natives and immigrants from Switzerland, 2006, Portuguese Economic Journal 5(2), 89-110 (with Philipp Bauer). [ pdf-download ] Heterogeneity in the Intergenerational Transmission of Educational Attainment: Evidence from Switzerland on Natives and Second Generation Immigrants, 2007, Journal of Population Economics 20(1), 121-148 (with Philipp Bauer). [ pdf-download ] Seniority in Germany: New Evidence on Returns to Tenure for Male Full-time Workers, 2008, Zeitschrift für Arbeitsmarktforschung (Journal for Labour Market Research) 41(2-3),139-156 (with Robert Orlowski). [ pdf-download ] Intergenerational Transmission of Educational Attainment in Germany - The Last Five Decades, 2009, Journal of Economics and Statistics (Jahrbücher für Nationalökonomie und Statistik) 229(1), 36-60 (with Guido Heineck). [ pdf-download ] Age at School Entry and Intergenerational Educational Mobility, 2009, Economics Letters 103(2), 87-90 (with Philipp Bauer). [ pdf-download ] The East German Wage Structure after Transition, 2009, Economics of Transition 17(4), 629-659 (with Robert Orlowski). [ pdf-download ] Kosten und Nutzen der Ausbildung an Tertiärbildungsinstitutionen im Vergleich, 2010, Perspektiven der Wirtschaftspolitik 11(2), 103-131 (with Martina Eschelbach, Guido Heineck, and Steffen Müller). [ pdf-download ] Kindergartenbesuch und intergenerationale Bildungsmobilität, 2010, Vierteljahreshefte der Wirtschaftsforschung 79(3), 121-132 (mit Philipp Bauer). [ pdf-download ] Female labor supply and parental leave benefits. The causal effect of paying higher transfers for a shorter period of time, 2011, Applied Economics Letters 18(1), 17-20 (with Annette Bergemann). [ pdf-download ] Evidence on Incentive Effects of Subjective Performance Evaluations, 2011, Industrial and Labor Relations Review 64(2), 241-257 (with Axel Engellandt). [ pdf-download ] Lohnentwicklung im Lebenszyklus - Eine Analyse von Ausmaß, Begründung und Heterogenität von Lohnsteigerungen, 2011, Zeitschrift für ArbeitsmarktForschung (Journal for Labour Market Research) 44(1), 29-41 (with Robert Orlowski). [ pdf-download ] The Effect of Secondary School Fees on Educational Attainment, 2010, forthcoming: Scandinavian Journal of Economics. [ pdf-download ] The Transition to Tertiary Education and Parental Background over Time, 2010, forthcoming: Journal of Population Economics (with Florian Schieferdecker). [ pdf-download ] The Welfare Use of Immigrants and Natives in Germany: The Case of Turkish Immigrants, 2011, Laser Discussion Paper No. 44, forthcoming: International Journal of Manpower (with Monika Sander and Christoph Wunder). [ pdf-download ] The Introduction of a Short-Term Earnings-Related Parental Leave Benefit System and Differential Effects on Employment Intentions, 2011, forthcoming: Schmollers Jahrbuch (with Annette Bergemann). [ pdf-download ] The Employment of Mothers - Recent Developments and their Determinants in East and West Germany, 2011, cesifo Discussion Paper No. 3189, forthcoming: Jahrbücher für Nationalökonomie und Statistik (Journal of Economics and Statistics) (with Barbara Hanel). [ pdf-download
WiSo-Import:2015-03-26:2652
Keywords: Review of Economics (Jahrbuch für Wirtschaftswissenschaften) 48(1); Refereed Publications: Determinanten des Rentenzugangs - Eine Analyse altersspezifischer Verrentungsraten (Determinants of Retirement Entry - An Analysis of Age-specific Retirement Rates); Labour Economics 6(2); Journal of Population Economics 12(3); Journal of Development Economics 56(2); Finanzarchiv 55(2); Applied Economics 29(5); 551-561. The Determinants of Child Mortality in the Philippines: Estimation of a Structural Model; 363-389. Labor Force Transitions of Older Married Couples in Germany; 281-305 (with David K. Guilkey). Immigrant Participation in the German Welfare Program; 229-251 (with David M. Blau). Disability Retirement Among Ge; 1999; 1998; 1997; 163-185. Income and Employment Effects of Health Shocks - A Test Case for the German Welfare State; 133-147 (with Peter Schmidt). Disability Retirement and Unemployment - Substitute Pathways for Labor Force Exit?